L.A. candy - Conrad, Lauren (New York : Harper, 2009)
When nineteen-year-old Jane Roberts is cast in a new reality show, she discovers that the fame and fortune of her new life come at a high price to herself and her friendships.
"A novel"--jacket.
Keywords: Reality television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Self-perception -- Juvenile fiction; Friendship -- Juvenile fiction; Conduct of life -- Juvenile fiction; Los Angeles (Calif.) -- Juvenile fiction